Number 32 (December 1995) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1995)
(December 1995) - Status of the Southern Redbelly Dace, Phoxinus erythrogaster, in Hatcher Bayou and Streams of the Yazoo Drainage, Mississippi. By William T. Slack, Martin T. O'Connell, Tanya L. Peterson, John A. Ewing, III, and Stephen T. Ross Constitution of the Southeastern Fishes Council (Revision, 20 April 1995) Contents of PROCEEDINGS
Keywords: southern redbelly dace; phoxinus erythrogaster; hatcher bayou; yazoo drainage; fishes